DEVELOPING IMAGE OF HIGHER EDUCATION PERFORMANCE - El Hariri, Ridwan (UPI Press, 2010)
This study aimed at acquiring actual profile and relationship of basic elements of educational institution performance in developing the image of Parahyangan university performance and implication to policy on quality assurance. A mixed methodology design covering quantitative and qualitative approaches was used. The qualitative approach aimed at 1) investigating the actual profile of Unpar performance and its relevance to the Performance Excellence for Education Criteria, and 2) investigating the alternative model of policy strategies in developing the image of excellent higher education performance in the future. While the quantitative approach aimed at testing hypothesis which specifically relates to the four aspects, namely, leadership, strategic planning, student and stakeholders and their influence to staff and faculty members focus and management process. Besides, it also investigated the relative contribution of brain center to the driver triad, work core, and outcomes in developing the image of Unpar performance. Results of the study consist of three main points, namely: 1) the description of Unpar performance; 2) the influence of leadership, strategic planning, student and stakeholder focus, staff and faculty focus, and management process on Unpar’s organizational performance results and the correlation between the brain center and driver triad, work core, and outcomes in Unpar, 3) the alternative model of development policy on the image of higher education performance.